Antibacterial and antifungal efficacy of Cajanus scarabaeoides seed extracts: A comparative study of solvent-based phytochemical extraction - Rajesh ROKKAM; Felicity PINIPAY; Killo J. TITUS; Satyanarayana BOTCHA; Raghavarao TAMANAM (Notulae Scientia Biologicae)
This study investigates the antibacterial and antifungal activities of various solvent extracts (ethyl acetate, hexane, methanol and chloroform) from Cajanus scarabaeoides seeds against both bacterial and fungal strains. The antibacterial activities were tested against gram-positive (Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus) and gram-negative bacteria (Vibrio cholerae, Salmonella paratyphi, Escherichia coli), while antifungal activities were examined against Candida albicans, Saccharomyces cerevisiae, and Aspergillus niger. The methanol extract exhibited the highest antimicrobial activity, particularly against S. aureus (12.67 mm inhibition), M. luteus (19.83 mm inhibition), S. paratyphi (12.33 mm inhibition), S. cerevisiae (12.50 mm) and A. niger (10.63 mm inhibition). Minimum inhibitory concentrations (MICs) demonstrated the potency of the methanol extract, especially with M. luteus (MIC of 27.83 µg/mL), S. paratyphi (28.50 µg/mL), and S. cerevisiae (28.80 µg/mL). Principal component analysis (PCA) revealed a strong correlation between phytochemicals like phenols, tannins, and flavonoids, and their antimicrobial effects, particularly against B. subtilis, S. paratyphi, and S. cerevisiae. The findings suggest that polar solvent methanol is more effective in extracting bioactive compounds responsible for antimicrobial and antifungal activities in C. scarabaeoides.